Enhancing Adolescent Girls Anemia Prevention Knowledge and Attitudes through Nutritional Consultations - Jumiyati, Jumiyati; Hendryani, Atika; Hidayati, Rinda Nur; W, Tetes Wahyu (Universitas Airlangga, 2024)
Anemia is a public health problem in Indonesia that can affect all age groups, from toddlers to the elderly, and primarily affects adolescents. One way to prevent anemia among them is by increasing knowledge and attitudes through nutritional consultation to achieve promotive and preventive efforts. In 2018, anemia in women was higher (27.2%) than in men (20.3%). This study aimed to determine the effect of nutritional consultations on the knowledge and attitudes of young women in preventing anemia in Bengkulu City. A quasi-experimental study with a non-randomized control group design, pre-test, and post-test design was conducted from October to November 2021 at SMP N 8 Bengkulu City. The intervention group subjects are 30 respondents, and at control group are 30 respondents; all were purposively selected. A paired T-test was used to analyse the effect of the intervention. The results showed a significant difference in the pre-test and post-test knowledge in the treatment group (p=0.002). At the same time, there was no significant difference between the pre-test and post-test knowledge of the control group (p=0.095). In comparison, the mean attitude before treatment did not differ between groups (p=0.048); each group showed differences after treatment. Intervention and control groups influence knowledge and attitudes before and after treatment (p=0.013).